Generalization of typology of national technology transfer centers - Zhurakovska, Maryana; Kravets, Anna; Shvets, Maryan (Видавництво Львівської політехніки, 2013)
The article addresses the operation peculiarities of national technology transfer centers. Existing technology transfer centers have been analyzed and the analogies have been drawn with the foreign models of such innovative structures. Operational experience of technology transfer centers in Ukraine has been generalized and their typology has been formulated.
Keywords: technology transfer center; innovative structure; technology transfer; innovative activity; typology